The Biochemistry and Effectiveness of Antioxidants in Food, Fruits, and Marine Algae - Lavinia Lorena Pruteanu; David Stanley Bailey; Andrei Cristian Grădinaru; Lorentz Jäntschi (MDPI AG, 2023)
It is more effective to maintain good health than to regain it after losing it. This work focuses on the biochemical defense mechanisms against free radicals and their role in building and maintaining antioxidant shields, aiming to show how to balance, as much as possible, the situations in which we are exposed to free radicals. To achieve this aim, foods, fruits, and marine algae with a high antioxidant content should constitute the basis of nutritional elements, since natural products are known to have significantly greater assimilation efficiency. This review also gives the perspective in which the use of antioxidants can extend the life of food products, by protecting them from damage caused by oxidation as well as their use as food additives.